Two decades after the implementation of Organic Law 5/2000: a look at forensic social work from a rights-based approach or perspective - Curbelo-Hernández, Emiliano A. (Acciones e Investigaciones Sociales, 2021)
Twenty years have passed since Organic Law 5/2000 came into force on 12 January regulating the criminal liability of minors and successive amendments (hereinafter referred to as LORRPM), with many changes being made to the framework of juvenile criminal justice in Spain. While it is true that the figure of the social worker already existed, this new regulation instituted a fresh approach, not only in criminal matters, but also anchoring the concept of social work as a professional forensic discipline, given the fact that Regulation 1774/2004, of 30 July, concerning the LORRPM, has established the basis for explaining in greater detail our functions and powers within technical teams. In line with the above, issues are presented relating to the collaboration and participatory and representative social intervention of the forensic social worker, from a rights-based perspective. By so doing, some procedural or methodological unknowns are revealed, enabling a mental framework of critical and reflective thinking to be fomented in the reader.